Can the Species Richness of Spiders be Determined? - Robert L. Edwards (Psyche: A Journal of Entomology)
The jackknife estimate of species richness for spiders in a study area on southwest Cape Cod was 373.1 species, with a confidence interval of 28.2 species. Over a period of six years 390 species had been recorded in that area. Fourteen habitats were sampled using conventional sampling techniques. The sample data for each habitat was examined for various aspects of comparability. It is suggested that for the purposes of calculating the jackknife estimate of species richness, a minimum number of individuals be collected from each habitat.